Clearing space for extreme psychologism about reasons. Issue 3 (2nd September 2016) - Mitova, Veli
Abstract : Are reasons for action facts or psychological states? There are two answers in the literature on the ontology of reasons. According to the Standard Story, normative reasons are facts, while motivating reasons are psychological states. According to the factualist, both normative and motivating reasons are facts. In this paper I argue that neither of these views is satisfactory. The Standard Story errs in thinking that the two kinds of reasons are different ontological entities. The factualist gets this right, but incurs some distasteful ontological commitments by thinking of motivating reasons as facts. We should, thus, give a proper hearing to the only serious logically possible alternative to the two existing views: both motivating and normative reasons are psychological states.